2015
DOI: 10.1002/2015je004895
|View full text |Cite
|
Sign up to set email alerts
|

Field investigation of dried lakes in western United States as an analogue to desiccation fractures on Mars

Abstract: Potential Desiccation Polygons (PDPs), tens to hundreds of meters in size, have been observed in numerous regions on Mars, particularly in ancient (>3 Gyr old) terrains of inferred paleolacustrine/playa geologic setting, and in association with hydrous minerals such as smectites. Therefore, a better understanding of the conditions in which large desiccation polygons form could yield unique insight into the ancient climate on Mars. Many dried lakebeds/playas in western United States display large (>50 m wide) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
(96 reference statements)
1
6
0
Order By: Relevance
“…Based on the statistical analysis of clay minerals occurring in different subclasses of Dalangtan PSSs, we made the following interpretation: The illite and chlorite compositions tend to appear in playa sediments associated with larger-sized PSSs, consistently with some previous studies, which points out that the formations of large desiccation polygons are related to lowering of groundwater levels under conditions of hydraulic diffusivity that are commonly associated with clay-dominated deposits (El Maarry, Watters, et al, 2015;Neal et al, 1968). The clay minerals are the main contributor to the development of large desiccation cracks on playa surfaces (El Maarry et al, 2014;Neal et al, 1968;Tucker, 1981).…”
Section: Sediment Composition Of Dalangtan Pss Terrainssupporting
confidence: 82%
“…Based on the statistical analysis of clay minerals occurring in different subclasses of Dalangtan PSSs, we made the following interpretation: The illite and chlorite compositions tend to appear in playa sediments associated with larger-sized PSSs, consistently with some previous studies, which points out that the formations of large desiccation polygons are related to lowering of groundwater levels under conditions of hydraulic diffusivity that are commonly associated with clay-dominated deposits (El Maarry, Watters, et al, 2015;Neal et al, 1968). The clay minerals are the main contributor to the development of large desiccation cracks on playa surfaces (El Maarry et al, 2014;Neal et al, 1968;Tucker, 1981).…”
Section: Sediment Composition Of Dalangtan Pss Terrainssupporting
confidence: 82%
“…The relatively high‐elevation terraced marginal terrains of the northern irregular depressions, which expose the underlying light‐toned materials by erosion, should have thicker clay‐bearing deposits relative to the lower center: this would cause larger volume changes and, consequently, form larger polygons at the higher topography areas. Terrestrial analog studies (e.g., El‐Maarry et al., 2015b; Neal et al., 1968) and previous modeling efforts (e.g., El‐Maarry et al., 2012) demonstrated that large desiccation polygons would form gradually due to that the tensile stresses (rise with desiccation) within clay‐dominated deposits would develop through lowering of a water table under condition of hydraulic diffusivity. For a long time of intense evaporation and lowering of groundwater levels, large fractures should have developed.…”
Section: Discussionmentioning
confidence: 99%
“…The globally distributed polygonal patterned grounds are the products of typical environments with hydrologic activity on the Earth and Mars (Bell, 2008;Carr, 2007;El-Maarry et al, 2015a, 2015bUlrich et al, 2011;Xiao et al, 2017). However, the polygonal landforms show a broad diversity in both morphologic characteristics and origins depending on their local geological settings (e.g., Dang et al, 2018;El-Maarry et al, 2013Helfenstein & Mouginis-Mark, 1980;Levy et al, 2009Levy et al, , 2010Seibert & Kargel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the present paper, our focus is primarily to discuss the brine analogy between salt flats on Earth and salty terrain on Mars. However, such salt flats in South America can be extremely useful for establishing many geological e.g., [48,111,112] and astrobiological e.g., [113,114] analogies. For example, as a future prospect, analogous research between the salt desiccation polygons in Salar de Uyuni and the cracks that are found in a recently discovered evaporated salt pond on Mars [115] (Figure 12) can be established to model the landscape evolution in such salt flats.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since a major water input to such continental salt flat systems is lateral inflow with minor contributions from direct rainfall (due to the atmospheric aridity) and the only output is evaporation [32], the surficial and hydrological changes in salt flat systems can be used as a proxy in studying the effects of climate change [47]. Terrestrial salt crack polygons and salt flat environments can function as Martian analogues e.g., [48] to understand Martian desiccation cracks e.g., [49] and extraterrestrial life e.g., [50]. In fact, aeolian processes acting on fluvial deposits are known to aid in the formation of polygonal patterns and dunes [29].…”
Section: Introductionmentioning
confidence: 99%